SIFAT ORGANOLEPTIK DAN UMUR SIMPAN MINUMAN HERBAL KUMANSI DENGAN PENAMBAHAN GULA BATU DAN GULA AREN - Lina Ivanti; Shannora Yuliasari; Wilda Mikasari; Dian Aprilia Kartika (Politeknik Pembangunan Pertanian Medan, 2022)
Herbal drinks were proven can increase body immunity, sothose werewidely consumed during this pandemic. The objective of this study were to examine the organoleptic characteristic and shelf life of herbal drinks that consist of turmeric, curcuma, and calamondin citrus with the addition of rock sugar and palm sugar. The research was conducted in March s.d. April 2021 at the Postharvest Laboratory of BPTP Bengkulu that include formulation stages, Total Dissolved Solids test (% Brix), organoleptic testing with 25 respondents, and shelf life test. The research design used Factorial Completely Randomized Design (CRD) with the addition of rock sugar and palm sugar at concentration of 5%, 10%, 15% and four replication. The data obtained were analyzed descriptively and statistically using analysis of variance (ANOVA). The results showed that the total dissolved solids increased with the addition of rock sugar and palm sugar concentrations. The treatment of adding rock sugar and palm sugar also had a significant effect on the taste of Kumansi herbal drinks but it was not significant to color, aroma, and viscosity at the 95% confidence level (P <0.05). In addition, Kumansi herbal drink with palm sugar has a longer shelf life than Kumansi with rock sugar.Herbal drink Kumansi was alternatif ready todrink herbal productfrom local raw material that was expected can increase those added value.